Science Information and the Public - A Review of Literature - David A. King (Journal of Applied Communications, 1984)
Informing the public about science: Is it an awful bore, or is it of critical importance to the survival of the world? This article is a review of literature that addresses this question. Most of the major research articles are reviewed and a bibliography is provided.